MC159 of Molluscum Contagiosum Virus Suppresses Autophagy by Recruiting Cellular SH3BP4 via an SH3 Domain-Mediated Interaction - Schmotz, Constanze (J Virol, 2019)
MC159 is a viral FLIP (FLICE inhibitory protein) encoded by the molluscum contagiosum virus (MCV) enabling MCV to evade antiviral immunity and to establish persistent infections in humans. Here, we show that MC159 contains a functional SH3 binding motif, which mediates avid and selective binding to SH3BP4, a signaling protein known to regulate endocytic trafficking and suppress cellular autophagy. The capacity to bind SH3BP4 was dispensable for regulation of NF-κB-mediated transcription and suppression of proapoptotic caspase activation but contributed to inhibition of amino acid starvation-induced autophagy by MC159. These results provide new insights into the cellular functions of MC159 and reveal SH3BP4 as a novel host cell factor targeted by a viral immune evasion protein. IMPORTANCE After the eradication of smallpox, molluscum contagiosum virus (MCV) is the only poxvirus restricted to infecting humans. MCV infection is common and causes benign skin lesions that usually resolve spontaneously but may persist for years and grow large, especially in immunocompromised individuals. While not life threatening, MCV infections pose a significant global health burden. No vaccine or specific anti-MCV therapy is available. MCV encodes several proteins that enable it to evade antiviral immunity, a notable example of which is the MC159 protein. In this study, we describe a novel mechanism of action for MC159 involving hijacking of a host cell protein called SH3BP4 to suppress autophagy, a cellular recycling mechanism important for antiviral immunity. This study contributes to our understanding of the host cell interactions of MCV and the molecular function of MC159.